IDENTIFIKASI BENTUK KEARIFAN LOKAL DALAM PENGELOLAAN AGROFORESTRI TRADISIONAL DI KABUPATEN NAGEKEO, PROVINSI NUSA TENGGARA TIMUR - Fransiska - Ule; Fransiskus Xaverius Dako; Yakub - Benu; Flora Evalina Ina Kleruk (JURNAL HUTAN LESTARI, 2023)
Mixed gardening is a form of traditional agroforestry whose management is carried out from generation to generation. The people of Jawapogo Village refer to mixed gardens as uma. Uma is a land management system that has been practiced by farmers and developed in the community according to local wisdom. Local wisdom is a custom and habit carried out by a group of people from generation to generation that is still maintained by indigenous peoples in certain areas. This study aimed to find out the form of local wisdom used by the Jawapogo Village community in managing uma. This research was carried out from September to November 2021 in Jawapogo Village, Nagekeo Regency. This data collection method was carried out through in-depth interviews with farmers, who were respondents, and also with traditional leaders using a questionnaire. The data is then presented descriptively using data analysis techniques, which consist of three paths: data reduction, data presentation, and drawing conclusions. Based on the results of the research, traditional agroforestry management in Jawapogo Village, Nagekeo Regency, has several forms of local wisdom, namely: Lera Ie, which usually occurs the day after the funeral of a deceased person, and on that day the community is not allowed to carry out activities on the land; Ti'i Ka Ebu Kajo, which is a gift eaten to the ancestors and done before and after planting; and Voe, which means doing a work in mutual cooperation. and Mendi persembahan Lau Gereja, which means giving offerings to the church.